Randomized trial of smartphone application and bed sensor for atrial fibrillation detection in high-risk patients - Lehto, Joonas; Nuotio, Joel; Relander, Arto; Jaakkola, Jussi; Lahdenoja, Olli; Vasankari, Tuija; Anzanpour, Arman; Elnaggar, Ismail; Rekola, Rami; Sandelin, Jonas; Hurnanen, Tero; Airaksinen, Juhani K. E.; et al. (Springer Nature, 2026)
This two-arm single-center exploratory randomized controlled trial evaluated the efficacy of prolonged rhythm monitoring in atrial fibrillation (AF) detection after an invasive cardiac procedure. Altogether 150 patients were enrolled. In the intervention group (IG), a bed sensor (EMFIT QS) and twice-daily smartphone recordings (CardioSignal app) were used, followed by a 12-lead ECG and a continuous three-to-seven-day ECG monitoring if alerts occurred. The control group (CG) received usual care. Overall, 78 patients were assigned to the IG and 72 to CG. During the three-month follow-up, AF was detected in 6/78 (7.7%) patients in the IG and in 0/72 (0.0%) in the CG (absolute risk difference 7.7%, 95% CI 1.8–13.6%, p = 0.029). After exclusion of patients who withdrew before the 3-month follow-up, 33/68 (48.5%) patients had alarms not leading to ECG-verified AF diagnosis, indicating that the current approach, in its present form, is not suitable for routine clinical implementation. Future studies should concentrate on minimizing alarms not leading to AF diagnosis when developing these novel non-ECG-based technologies. ClinicalTrials.gov Identifier: NCT05351775, 2022/04/28.